HIV awareness campaigns, Knowledge and practices among pregnant women living with HIV in northern Uganda - Ogena, Jonathan; Opii, Didan Jacob; Nakku, Betty; Aceng, Cindrella; Oola, Tonny; Kobusinge, Veronica; Rukundo, Godfrey Zari; Auma, Anna Grace (PAMJ One Health, 2023)
Introduction: despite significant progress made in HIV care and research, there are still many misconceptions on acquisition, treatment and progress of HIV especially in rural communities. Different strategies have been utilized to spread reliable knowledge to different audiences. One of the strategies has been the use of community awareness campaigns. However, it is not clear if these campaigns have been effective and if they reached the different sub-populations in the community. This study aimed to assess the knowledge and practices of HIV community awareness campaigns and associated factors among pregnant women living with HIV in Oyam district in northern Uganda. Methods: it was a quantitative cross-sectional study in a consecutively selected sample of 416 pregnant women living with HIV. An interviewer-administered questionnaire was used to collect data on awareness, sources of information, content of the messages, utilization of the awareness messages and the perceptions about the campaigns. In addition, we determined factors associated with knowledge about the community campaigns. The level of knowledge was determined by the participant' response indicating whether they had prior knowledge about awareness campaigns or not. Data were analyzed using SPSS version 23 using Chi-square and logistic regression at 95% confidence interval and a p-value of 0.05 for statistical significance. Results: of the 416 participants in the study, 92.5% (n=385) had prior knowledge about HIV awareness campaigns and 97.6% (n=406) had specifically heard about anti-HIV-related stigma campaigns. The most common sources of information were radio (43.3%), health education sessions at health facilities (44%), and family members (2.9%). The received information was on HIV transmission, antiretroviral therapy, HIV related stigma as well the effect of stigma on self-esteem, hopelessness, HIV related abuse and ART adherence. Knowledge was associated with having a source of income (OR= 0.162, 95%CI 0.034-0.775, P= 0.023), having heard about HIV-related Stigma (OR=0.051, 95%CI 0.003-.949, P= 0.046), availability of community linkage facilitators (OR= 0.077, 95% CI 0.011-0.537, P= 0.010), use of awareness messages by community members (OR= 13.887, 95% CI 1.316-146.6, P=0.029) and the source of HIV awareness information (OR= 0.462, 95% CI 0.237-.902, P=0.024). Conclusion: although there is still high HIV-related stigma in general public, there is increased awareness among pregnant women. Availability of community linkage facilitators and use of appropriate sources of information seems to be helping with increasing community knowledge about HIV awareness campaigns.
Keywords: HIV awareness campaigns; Pregnant women; HIV; Uganda